Gene Doping in Sports : the Science and Ethics of Genetically Modified Athletes - Schneider, Angela Jo-Anne, 1959-; Friedmann, Theodore, 1935- (Advances in genetics, 2006)
Advances in genetics have begun to deliver on their promise of new and improved approaches to the prevention and treatment of human disease, including the gene-based therapeutics. The international sports community has begun to recognize the potential harmful use of gene transfer technology by athletes. The task of monitoring and controlling sports doping must be a truly cooperative effort, involving the cooperation of a range of local, national, and international organizations. There are very serious broad social and ethical issues at stake that relate to our definition of sports and its role in our society, as well as the social and ethical principles that are challenged or breached through sport doping, determining which forms of performance enhancement - in sport or any other realm of human activity - are acceptable, and what makes the enhancement of sport performance different from enhancement in other areas of human activity (e.g., cosmetic surgery, mood and learning enhancement through drugs, and drug-based "treatment" of physical and intellectual changes in normal aging process). This book tackles all these issues and more, serving as the first such focused treatment of this increasingly important topic, which has broad-based implications for science, medicine, sports, and society.